ANALISIS PENERAPAN ADMINISTRASI BERBASIS ONLINE TERHADAP KINERJA DAN LOYALITAS GURU SMAS IT FAJAR ILAHI 2 BATAM KEPULAUAN RIAU TAHUN 2024/2025 - Awalia, Viddinia; Al Mufti, Muflihin; Supangat, Supangat (UNISAN JURNAL, 2025)
This study aims to analyze the implementation of online-based administration and its impact on teacher performance and loyalty at SMAS IT Fajar Ilahi 2 Batam. The formulation of the problem in this study includes how the implementation of online-based administration in the school and its impact on teacher performance and loyalty. This study is expected to provide insight into the effectiveness of the administration system implemented in improving the performance and loyalty of educators The research method used is a qualitative approach with a descriptive design. This research was conducted at SMAS IT Fajar Ilahi 2 located in Batam, with research subjects consisting of teachers who teach at the school. The main data sources came from interviews, observations, questionnaires and documents related to school administration. Data collection techniques were carried out through semi-structured interviews, direct observation, questionnaires and document analysis, while data analysis techniques used the Miles and Huberman analysis model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of online-based administration at SMAS IT Fajar Ilahi 2 Batam has improved teacher performance and their loyalty. Teachers feel more organized and efficient in carrying out administrative tasks, which has a positive impact on student learning outcomes. The conclusion of this study is that online-based administration is effective in improving teacher performance and loyalty. The suggestion given is for schools to continue to develop and update online administration systems to support a better learning process.